Human D‐Lactate Dehydrogenase Deficiency: A Case Report in a Young Boy - T. B. Sloth; M. C. Ørngreen; J. Ek; I. Bache; F. Wibrand; A. M. Lund (JIMD Reports)
ABSTRACT D‐lactate is an isomeric form of lactate, which is almost undetectable in the circulation in individuals with normal lactate metabolism. Patients diagnosed with the disease human D‐lactate dehydrogenase deficiency present with elevated plasma D‐lactate, causing D‐lactic acidosis, which can be associated with neurological symptoms. This paper reports a Danish patient presenting with delayed psycho‐motor development and metabolic acidosis. Whole genome sequencing (WGS) revealed a homozygous 0.1 Mb loss of the long arm of chromosome 16 involving 3 protein coding genes, CTRB2, ZFP1, and exon 1–7 of the LDHD gene (NM_194436.3c: 1_930del, p.M1_Q310del), which encodes the human D‐lactate dehydrogenase enzyme. Metabolic screening of the plasma and urine demonstrated elevated levels of D‐lactate. Based on the genetic and biochemical findings, the patient was diagnosed with human D‐lactate dehydrogenase deficiency. Biochemical and molecular studies, including WGS, did not disclose any additional pathogenic findings. This report compares the laboratory and clinical findings in our patient with observations in other patients diagnosed with human D‐lactate dehydrogenase deficiency described in the literature. The comparison shows that the clinical symptoms vary among patients with pathogenic variants in the LDHD gene, but an elevated level of D‐lactate in plasma and urine is found in all patients. Some reported patients had additional diseases, while the boy reported here was most probably solely affected by D‐lactate dehydrogenase deficiency, making the clinical picture clearer. Take‐home message: Human D‐lactate dehydrogenase deficiency can be caused by pathogenic variants of the LDHD gene, and shows a broad phenotypic variability, with some patients only having increased plasma urate/gout and others neurological findings and psycho‐motor developmental delay.